The persistence of trade relocation from civil conflict - Korn, Tobias; Stemmler, Henry (Journal of development economics, 2025)
This paper examines the lasting impact of civil conflicts on bilateral trade flows and the subsequent implications for economic recovery. Utilizing a novel estimation approach based on the structural gravity model of international trade, we demonstrate that importers shift their trade preferences away from exporters involved in civil conflicts. This effect persists even after the conflict has been resolved, as countries solidify their relocation decisions by reducing bilateral trade costs with alternative trading partners through Preferential Trade Agreements. Notably, the persistent trade relocation is more pronounced in the manufacturing sector, while it does not occur in the fuels sector. Our findings underscore the significance of supportive trade policies as effective tools for assisting nations in recovering from episodes of political violence. Furthermore, our estimation approach can be adapted to investigate the impacts of other unilateral shocks, such as natural disasters, or to analyze various bilateral dependent variables, including migration.
Online veröffentlicht: 26 September 2024
Keywords: Erde; Aufsatz in Zeitschrift